STUDI TINJAUAN PUSTAKA HUBUNGAN FILSAFAT PENDIDIKAN DENGAN PENGEMBANGAN BERPIKIR KRITIS DAN KREATIF PADA MAHASISWA - Ayu Listiana; Ismail (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the relationship between educational philosophy and the development of critical and creative thinking skills in students through a literature review. This study was conducted by examining various international and national literature discussing the role of educational philosophy in the learning process in higher education. The results of the study show that educational philosophy plays an important role in shaping students' thinking paradigms through reflective, dialogical, and humanistic approaches. Philosophical approaches such as constructivism, pragmatism, and existentialism have proven to be relevant in developing critical and creative thinking skills. In addition, problem-based learning strategies, philosophical discussions, and reflective learning are effective means of implementing the values of educational philosophy. In conclusion, educational philosophy not only serves as a theoretical foundation but also as a practical instrument in creating a learning environment that fosters students' critical and creative thinking skills.